The Diversity and Composition of Assemblages of Water Beetles (Gyrinidae, Dytiscidae, Hydrophilidae) in a Peat Bog in Belarus - Shatarnova, O. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2021)
Peat bogs of Europe are ecosystems with very specific extremely environmental conditions. Among peat bog water bodies are lakes, streams and hollows, which are characterized by strongly acidic and mineral poor water. However, the diversity of the inhabitants of the peat water environment is very poorly investigated. The aim of this study was to examine the water beetle diversity and species composition in the peat bog of Belarus. In total, 45 species of water beetles belonging to 3 families (Gyrinidae, Dytiscidae, Hydrophilidae) were sampled by entomological net. Among them specialised tyrphophilous species were Hydroporus erythrocephalus, H. incognitus, H. melanarius, H. obscurus, H. tristis, Ilybius aenescens, Rhantus sututellus, Enochrus affinis, E. ochropterus. A rather high diversity was recorded (Shannon index H’= 2.037–2.912). The highest diversity for water beetles was in lakes.